2022
DOI: 10.1590/fst.59321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the breeding value of Holstein black-and-white stud bulls in the Republic of Kazakhstan

Abstract: Currently, the dairy cow industry's primary goal is to reach maximum indicators in the manufacture of high-quality goods. It is necessary to utilize high-quality animals in breeding and productive qualities to attain this goal. Numerous research and practical works have proven that stud bulls have a major impact on the genetic effect of animal stock correction: proper stud bull selection ensures maximal genetic development in animal production. Animals of the Holstein breed of various selections are used to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The analysis of the results obtained for the aggregate estimation period showed that when using information for two adjacent years, firstly, the number of daughters per one estimated bull increases (to 52.4%), and secondly, the average number of effective daughters increases (up to 51.5%) per one tested bull and thirdly, the average number of effects of HYS factors increases (up to 43.1%), per one servicing bull (Zheksembekovich et al, 2020). In particular, black-and-white cattle are capable of producing 4936-6761 kg of milk, with a mass fraction of 3.80-3.96% fat in milk and 3.28-3.40% protein (Zhumanov et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the results obtained for the aggregate estimation period showed that when using information for two adjacent years, firstly, the number of daughters per one estimated bull increases (to 52.4%), and secondly, the average number of effective daughters increases (up to 51.5%) per one tested bull and thirdly, the average number of effects of HYS factors increases (up to 43.1%), per one servicing bull (Zheksembekovich et al, 2020). In particular, black-and-white cattle are capable of producing 4936-6761 kg of milk, with a mass fraction of 3.80-3.96% fat in milk and 3.28-3.40% protein (Zhumanov et al, 2022).…”
Section: Resultsmentioning
confidence: 99%